Analysis of Thematic Structure of Researches in Medical Anthropology Field - Fathemeh Makkizadeh; Abolfazl Asadnia; Malihe Alimondegari; Fezzeh Ebrahimi (مدیریت اطلاعات سلامت, 2022)
Introduction: New applications of studies to draw the structure of science including clustering concepts and identifying new fields of studies. This study was co-word analysis of intellectual structure of knowledge in the field of throbbing headaches.Methods: The research was conducted adopting a scientometric approach to content analysis of texts using the co-words and social network analysis. A total of 1311 documents were identified from the Topic="Medical Anthropology" search strategy in the WOS database. Data analysis was been done through cluster analysis method and strategic diagram.Results: The findings related to clustering led to the formation of eight thematic clusters: "Biomedical Anthropology", "AIDS and Covid-19 (epidemics)","Medical Anthropology with a Spiritual Approach", "Economic Medical Anthropology", "Ethnic Medicine", "Medical Anthropology" Applied", "Education and culture of health" and "Anthropology of reproduction". "AIDS and Covid-19 (epidemics)" was determined to be the highest centrality and density cluster.Conclusion: Using co-word analysis, it is possible to determine the scientific structure of a field. According to the frequency of keywords and clusters obtained from the strategic diagram, it was revealed that the thematic fields of AIDS and Covid-19 (epidemics) are the important emerging fields in this field.